The Influence Of Employee Selection On Employee Performance With Career Development As A Mediation Variable Case Study At PT Ilmukomputercom Braindevs Sistema - Sonia Christine Panjaitan; Agus Sugiarto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Employee performance is very important in the company to be able to achieve the goals set. Various efforts can be made to improve employee performance, including by knowing what factors can affect employee performance. The purpose of this study was to partially examine the effect of selection and employee career development on employee performance at PT IlmuKomputerCom Braindevs Sistema as well as the effect of employee selection on employee performance with career development as a mediating variable. The population in this study was 40 employees of PT IlmuKomputerCom Braindevs Sistema. Sampling in this study used a sampling technique, namely using all employees of PT IlmuKomputerCom Braindevs Sistema as samples in the study. The data collection technique used in this study was a questionnaire. The data analysis technique used is a quantitative analysis technique using the t test and Sobel test. The results of data analysis show that partially selection and employee career development have an effect on employee performance at PT IlmuKomputerCom Braindevs Sistema with a sig value t-table.